IN SILICO ANALYSIS OF INCREASING AFFINITY OF DNA POLYMERASE ENZYMES FROM PYROCOCCUS WOESEI AND THERMUS SCOTODUCTUS FUSED WITH DNA-BINDING PROTEINS SSH10 AND SAC7D - Azaria Alma Puteri, Mathilda
Thermostable DNA polymerase is an essential enzyme for diagnostic purposes such as PCR tests. Usually, it is used to rapidly copies the DNA chain in the PCR test. The PCR reaction can be inefficient if there is a weak affinity between the DNA polymerase and the target DNA. There are many ways to increase an enzyme’s affinity, one of them is by fusing DNA polymerase and DNA binding protein. This research focuses on designing protein fusion candidates using an in-silico approach to improve DNA polymerase affinity. Fusing Pwo DNA polymerase (NCBI-ProteinID: U84155.1), Tsk1 DNA polymerase (NCBI-ProteinID: MW080815.1) as the DNA polymerase enzyme, and SSH10 (NCBI-ProteinID: AJ298830.1), Sac7d (NCBI-ProteinID: AAY79492.1) as the DNA-binding protein, increased enzyme quality. The molecular weight and index instability of all protein candidates calculated using the ProtParam tool. 3D structure of protein candidates predicted using the trRosetta server. Evaluating the tertiary structure of each protein candidate was done by YASARA, Fold X, SAVES, ProSA, and Molprpbity server. For the next step, The selected enzyme was docked by the ligand using the HADDOCK server. Molecular interaction between the proteins and the ligands visualized using the LigPlot program. Codon optimization for the nucleotide sequence of the fusion protein done using JCat. Then the optimized gene was constructed in bacterial expression vector PET23a using the SnapGene tool. This research shows that Pwo_Sac7d is the chosen candidate. The predicted HADDOCK score for this enzyme is -167.2, the predicted Z-score is 1.9, with an RMSD value of 0.6 Å, binding energy of -10.34 kcal/mol, and Gibb’s free energy of -195.88 kcal/mol. It showed around 29 potential interactions between Pwo_sac7d and the ligands, where 13 of them are the key residues located on the palm and thumb side of the DNA polymerase. The result of optimized DNA sequences shows that the CAI value was 0.86, and the GC content was 46.2%. The results of this study indicate that the Pwo_Sac7d fusion protein has better affinity than native PWO DNA polymerase. The DNA sequence of the fusion enzyme has been successfully constructed on the pET23a expression vector and predicted to be expressed in the recombinant bacterial system. Further research is needed to confirm the results of the in silico design.